Houdini : his legend and his magic - Henning, Doug.; Reynolds, Charles R. (New York : Times Books, 1977)
A biography of the magician who became famous for his ability to escape almost any form of restraint. Describes his 10 greatest illusions as they appeared to audiences in the early 1900's
Keywords: Houdini, Harry, -- 1874-1926.; Magicians -- United States -- Biography; Escape artists -- United States -- Biography -- Juvenile literature